2007
DOI: 10.1111/j.1365-2648.2007.04395.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled evaluation of a theory‐based postpartum sexual health education programme

Abstract: The longer-term effectiveness of our theory-based interactive postpartum sexual health education programme will be enhanced by matching teaching strategies to participants' stage of learning preparedness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 29 publications
3
15
0
Order By: Relevance
“…The latter can also affect the child and his or her sexual development (Jug Došler, 2015). In addition, Lee and Yen (2007) call attention to the fact that health care professionals should play a more active role and more openly discuss sexual activity and (lack of) sexual pleasure with both partners during the first postpartum check-up with the gynaecologist. They came to the conclusion that individualised approach is the most appropriate form of sex education in the postpartum period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter can also affect the child and his or her sexual development (Jug Došler, 2015). In addition, Lee and Yen (2007) call attention to the fact that health care professionals should play a more active role and more openly discuss sexual activity and (lack of) sexual pleasure with both partners during the first postpartum check-up with the gynaecologist. They came to the conclusion that individualised approach is the most appropriate form of sex education in the postpartum period.…”
Section: Resultsmentioning
confidence: 99%
“…The childbearing period is a very vulnerable time in the sex life of a woman or a couple. Generally, sexual activity and intimacy significantly decrease during pregnancy, which can last up to several months after childbirth (Lee and Yen, 2007;Rezaee and Kinsberg, 2012;Boyd et al, 2013). Sexuality after childbirth includes much more than just a physical act of stimulating the genitalia.…”
mentioning
confidence: 99%
“…A flowchart of included studies can be found in Figure . Twenty‐three studies took place in the USA, one study was located in both the USA and Puerto Rico, and the remaining studies were located in Australia, New Zealand, Madagascar, Mexico, South Africa, Taiwan and the UK . The smallest sample size was 89, the largest was 38 635 .…”
Section: Resultsmentioning
confidence: 99%
“…The content of the interventions ranged from audio/visual, risk assessment, didactic, skill building/motivational interviewing, and providing resource lists …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation